(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In recent times, soil erosion becomes very critical environmental problems which causes severe range of land degradation. Sediment yield caused by deterioration process of soil by which occurred due to the physical movement of soil particles on land surface. This study aimed at estimation of sediment yield in Mubi South Watershed, with the aid of geospatial technology. The following data were used for the research; soil, rainfall, ASTER, sentinel 10 m satellite of the year 2016. Factor maps were generated for all the data which served as input layer for the SLEMSA model in estimation of sediment yield in the study area. It was found that, the magnitude of the soil loss was about 4.033 tons/ha/year. Also, the sediment yield was about 148.43 tons/ha/year. The research recommended a good soil loss management so as to reduce land degradation, soil loss and sedimentation within the watershed for planning and implementation of watershed management, degraded land restoration